The Pheochromocytoma - diagnosis and treatment, review of literature - Bartosz Skierkowski; Alicja Baranowska; Katarzyna Baranowska; Filip Czyżewski; Kinga Filipek; Jakub Kawka; Michał Muciek; Sebastian Mrugała; Waldemar Mrugała; Natalia Zalewska (Nicolaus Copernicus University in Toruń, 2024)
Introduction: Pheochromocytomas are rare tumors originating from the adrenal medulla, which can occur sporadically or as part of hereditary syndromes. Many patients with chromaffin tumors harbor genetic mutations, typically inherited in an autosomal dominant manner, hence genetic testing is recommended for all patients. Symptoms can result from both excessive catecholamine production and the mass effect of the tumor. Diagnosis is confirmed by elevated levels of metanephrines or normetanephrines in the plasma or urine. Radiological imaging aids in tumor localization and assessment of potential local invasion or metastasis. Preoperative preparation of all patients involves the use of α-receptor blockers and/or other medications to control arterial hypertension, arrhythmias, and fluid volume. Surgery remains the treatment of choice, with lifelong follow-up recommended. Objective: The review article aims to provide an overview of chromaffin tumor pathology, their etiology, discuss diagnostic possibilities, and indicate therapeutic options for patients. Materials and Methods: A summary of reports available in medical publications and scientific studies found in databases such as PubMed, CrossRef, Google Scholar, as well as relevant textbooks. Results: Chromaffin tumors are rare but dangerous for patients; adequate pharmacological preparation for surgery, which is usually necessary, is extremely important. Conclusions: The main role is to establish the correct diagnosis, or even suggest and conduct diagnostic tests towards a chromaffin tumor. Patient management involves controlling blood pressure, appropriate premedication, and surgical intervention. After such treatment, patients require continuous monitoring to detect any potential disease recurrence.